Far-infrared photometry of OJ 287 with the Herschel Space Observatory - Mark Kidger; Staszek Zola; Mauri Valtonen; Anne Lähteenmäki; Emilia Järvelä; Merja Tornikoski; Joni Tammi; Alexis Liakos; Gary Poyner (EDP SCIENCES S A, 2022)
Context: The blazar OJ 287 has shown a approximate to 12 year quasi-periodicity over more than a century, in addition to the common properties of violent variability in all frequency ranges. It is the strongest known candidate to have a binary singularity in its central engine.
Aims: We aim to better understand the different emission components by searching for correlated variability in the flux over four decades of frequency measurements.
Methods: We combined data at frequencies from the millimetric to the visible to characterise the multifrequency light curve in April and May 2010. This includes the only photometric observations of OJ 287 made with the Herschel Space Observatory: five epochs of data obtained over 33 days at 250, 350, and 500 mu m with Herschel-SPIRE.
Results: Although we find that the variability at 37 GHz on timescales of a few weeks correlates with the visible to near-IR spectral energy distribution, there is a small degree of reddening in the continuum at lower flux levels that is revealed by the decreasing rate of decline in the light curve at lower frequencies. However, we see no clear evidence that a rapid flare detected in the light curve during our monitoring in the visible to near-IR light curve is seen either in the Herschel data or at 37 GHz, suggesting a low-frequency cut-off in the spectrum of such flares.
Conclusions: We see only marginal evidence of variability in the observations with Herschel over a month, although this may be principally due to the poor sampling. The spectral energy distribution between 37 GHz and the visible can be characterised by two components of approximately constant spectral index: a visible to far-IR component of spectral index alpha = -0.95, and a far-IR to millimetric spectral index of alpha = -0.43. There is no evidence of an excess of emission that would be consistent with the 60 mu m dust bump found in many active galactic nuclei.